1992
DOI: 10.21273/jashs.117.6.902
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Applications of Potassium Silicate Reduce Severity of Powdery Mildew on Cucumber, Muskmelon, and Zucchini Squash

Abstract: The effect of soluble potassium silicate applied to cucumber (Cucumis sativus L.), muskmelon (C. melo L.), and zucchini squash (Cucurbita pepo L.) on the severity of powdery mildew was examined. Application methods included amending nutrient solutions to a concentration of 1.7 mm Si and foliar sprays containing 1.7, 8.5, 17, and 34 mm Si. Untreated plants and plants sprayed with distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(74 citation statements)
references
References 10 publications
3
70
0
1
Order By: Relevance
“…In this method, a hydrophobic layer of particles keep water physically separated from the plant surface which helps in suppressing several diseases such as powdery mildew, sooty blotch, fly speck, and fire blight Mendgen et al, 1992;Menzies et al, 1992). The particulate material did not interfere with the action of conventional bactericides, fungicides or pH modifying agents.…”
Section: Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, a hydrophobic layer of particles keep water physically separated from the plant surface which helps in suppressing several diseases such as powdery mildew, sooty blotch, fly speck, and fire blight Mendgen et al, 1992;Menzies et al, 1992). The particulate material did not interfere with the action of conventional bactericides, fungicides or pH modifying agents.…”
Section: Diseasesmentioning
confidence: 99%
“…Potassium silica application was effective in reducing powdery mildew in apple Menzies et al, 1992). White wash was useful in suppressing the transmission of citrus stubborn disease (Gumpf et al, 1981) and papaya decline (Franck and Bar-Joseph, 1992).…”
Section: Diseasesmentioning
confidence: 99%
“…However, there is no strong evidence that Si can be absorbed by leaves and few scientific studies have confirmed the benefits of Si amendments through foliar applications. Some positive effects have been reported on cucumber, muskmelon, zucchini and grape to control powdery mildews Menzies et al 1992). Nevertheless, for those studies, Si concentrations of 17 mM in the form of potassium silicate were reportedly used which far exceeds the standard 1.7 mM in root applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the defense mechanisms enhanced by Si is the formation of a physical barrier below the cuticle after monosilicic acid polymerization as well as an increase in the concentrations of total soluble phenolics and phytoalexins and higher activity of defense enzymes (18,33). In dicotyledonous plants such as cucumber, melon, and pumpkin, foliar applications of potassium silicate (KSi) reduced the number of colonies of Sphaerotheca fuliginea (23). On bean, foliar application of sodium silicate decreased the area under anthracnose progress curve by 62% (25).…”
mentioning
confidence: 99%